2016
DOI: 10.1039/c6ra09703k
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry-controlled cycloaddition of nitrilimines with unsymmetrical exocyclic dienones: microwave-assisted synthesis of novel mono- and dispiropyrazoline derivatives

Abstract: The Microwave-assisted 1,3-dipolar cycloaddition of (E,E)-1,3-bisarylidenetetral-2-ones with nitrilimines affords a series of mono- and dispiropyrazolines in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…1) in accordance with our previous work on ( E , E )-bis(arylidene)tetral-2-ones vis-à-vis nitrilimines. 55 Furthermore, if we depict the QTAIM population results on the optimized ( E , E ) isomer we are able to confirm a discrepancy in the reactivity between its double bonds. Considering the electronic density of the bond critical points values, the DB associated with the 3-position presents a BCP electronic density of about 0.334 a.u., whereas the DB at position 1 reports a lower ρ value in its BCP (about 0.328 a.u.).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…1) in accordance with our previous work on ( E , E )-bis(arylidene)tetral-2-ones vis-à-vis nitrilimines. 55 Furthermore, if we depict the QTAIM population results on the optimized ( E , E ) isomer we are able to confirm a discrepancy in the reactivity between its double bonds. Considering the electronic density of the bond critical points values, the DB associated with the 3-position presents a BCP electronic density of about 0.334 a.u., whereas the DB at position 1 reports a lower ρ value in its BCP (about 0.328 a.u.).…”
Section: Resultsmentioning
confidence: 81%
“…This result is in agreement with our hypothesis as already demonstrated with nitrilimines as 1,3-dipoles that afford spiropyrazolines. 55…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…103 The reaction affords the spirocycle 251 in the presence of the catalyst 249 and DABCO in DCM, while the for- Later Gazzeh and co-workers accomplished a Microwave assisted synthesis of mono and dispiropyrazolines (256 and 257). 105 It is a 1,3-dipolar cycloaddition reaction of in situ generated nitrilimines with exocyclic dienones 254 (Scheme 95). The outcome of the reaction is highly controlled by the stoichiometry of the hydrazonyl chloride 255 which is the precursor of nitrilimine.…”
Section: Synthesis Of Other Spiroheterocyclesmentioning
confidence: 99%
“…Disubstituted alkenes are typically competent substrates, with trisubstituted olefins reacting more sluggishly [ 9 ]. Nitrile imines are also effectively applied in the cycloaddition reaction with exocyclic alkenes [ 10 ] to form spirocyclic products containing 4-substituted [ 11 ] or 5-substituted pyrazole/pyrazoline cycles [ 12 ]. However, it has been shown that generally intermolecular nitrile imine cycloadditions favors the formation of a regioisomer with the most sterically encumbered substituent of the dipolarophile in the 5-position of the resulting heterocycle [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%